Pragmatic analysis of verbal attacks in Indonesian courtrooms: Exploring prevalence, nature, and cultural influences - Syahfitri Purnama (Indonesian Journal of Applied Linguistics, 2023)
This study investigated the pragmatic aspects of verbal attacks within Indonesian courtrooms, specifically examining speech acts and their alignment with Grice's maxims. While previous research has explored verbal attacks in legal contexts, this study is expected to fill a gap in the literature by focusing on the pragmatic analysis of speech acts and Grice's maxims in Indonesian settings. Using a qualitative research approach and court transcripts, the speech acts contained in this research were systematically analyzed and categorized based on the type and illocutionary force while scrutinizing their adherence to Grice's maxims. The findings reveal a diverse range of speech acts deployed during verbal attacks, including assertive challenges and veiled accusations, often involving deliberate violations of Grice's maxims. Participants strategically flout maxims, utilizing implicatures to contribute to the confrontational nature of verbal attacks. This study is also expected to advance our understanding of the pragmatic dimensions of verbal attacks in Indonesian courtrooms and to describe the strategic use of language in the legal context. It has the potential to inform legal practice, enhancing comprehension of courtroom communication and promoting more effective and respectful exchanges within the Indonesian legal system.